Analysis of The Meaning of Restitution of State Losses As The Abolishment of Corruption Crimes - Bonny, Michael Nicholas; Lisi, Ivan Zairani; Hamzah, Herdiansyah (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study aims to analyze the return of state financial losses as the abolishment of corruption crimes contained in the Circular Letter of the Attorney General Republic Indonesia Number B 1113/F/Fd.1/05/2010 concerning Priorities and Achievements in Handling Corruption Cases in point 1 which essentially states that people who return state losses due to corruption crimes can be given relief to abolish the criminal elements committed. The research uses a doctrinal. The results of the study show that the return of state losses committed by the perpetrators of corruption crimes cannot be used as a reason either to abolish the authority to prosecute corruption cases that are being investigated or as a reason for the abolition of corruption crimes committed by suspects, but the return of state losses is a reference for the judges to consider imposing criminal sanctions on the perpetrators as factors that mitigated him when he was submitted to the court as contained in Article 4 of the Law on the Eradication of Corruption [Penelitian ini bertujuan untuk menganalisis pengembalian kerugian keuangan negara sebagai penghapusan tindak pidana korupsi yang tertuang dalam Surat Edaran Jaksa Agung RI Nomor B 1113/F/Fd.1/05/2010 tentang Prioritas dan Capaian dalam Penanganan Kasus Korupsi pada poin 1 yang pada dasarnya menyatakan bahwa orang yang mengembalikan kerugian negara akibat tindak pidana korupsi dapat diberikan keringanan untuk menghapuskan unsur tindak pidana yang dilakukan. Penelitian ini menggunakan doktrinal. Hasil penelitian menunjukkan bahwa pengembalian kerugian negara yang dilakukan oleh pelaku tindak pidana korupsi tidak dapat dijadikan alasan baik untuk menghapuskan kewenangan penuntutan kasus korupsi yang sedang ditelusut atau sebagai alasan penghapusan tindak pidana korupsi yang dilakukan oleh tersangka, namun pengembalian kerugian negara menjadi acuan bagi hakim untuk mempertimbangkan menjatuhkan sanksi pidana kepada pelaku sebagai faktor yang meringankan dia ketika diajukan ke pengadilan sebagaimana tertuang dalam Pasal 4 Undang-Undang Pemberantasan Korupsi]